The influence of the development of soft competencies and hard competencies on the performance of Perum Bulog employees in the internal supervision division - Enrico Alfriano Ramadhan; Herayati Herayati; Martinus Wahyu Purnomo (Institute of Computer Science (IOCS), 2023)
Based on the author's observations, several employee performance issues are apparent, with problems existing in both soft competencies and hard competencies. This situation can have a negative impact on the company. The objective of this research is to determine the influence of the development of soft competencies and hard competencies on the performance of Perum BULOG employees in the Internal Oversight Division. The method used is quantitative statistics with three variables: soft competencies (X1), hard competencies (X2), and employee performance (Y), with a sample of 32 respondents who are Perum BULOG employees in the Internal Oversight Division. The research results indicate that the t-test result for variable X1 shows that it does not have a partial and significant influence on Y, as the calculated t-value is -231 < the tabled t-value of 1.701, and the significance value for variable X1 is 0.819 > 0.05. Therefore, Ho (null hypothesis) is accepted, and H1 (alternative hypothesis) is rejected. The t-test result for variable X2 indicates that it has a partial influence on Y, as the calculated t-value is 26.666 > the tabled t-value of 1.701, and the significance value for variable X2 is 0.000 < 0.05. The analysis of the F-test yields a significance value of 0.000 < 0.05, indicating that, collectively, variables X1 and X2 significantly influence Y. The tabled F-value is 3.340, while the calculated F-value is 399.149 > 3.340 (F-table). Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.